Analysing the trade-off between transparency and efficiency in the Council of the European Union. Issue 1 (2nd January 2020) - Novak, Stéphanie; Hillebrandt, Maarten
ABSTRACT: This article analyses the oft-invoked tension between transparency and efficiency in the context of the Council of the European Union. It asks to what extent these two sources of legitimacy are incompatible, by exploring the premises and the coherence of the trade-off argument. It argues that the argument is unclear because of the multiple meanings of efficiency. Furthermore, while the trade-off is in some instances more plausible than in others, transparency does not necessarily threaten efficiency and can sometimes even increase it. The presumed correlation between secrecy and efficiency, on which the trade-off is implicitly based, can also be questioned on theoretical and empirical grounds. For these reasons, the trade-off argument forms a generally contingent and often questionable basis for limiting transparency.